Nyau masquerade performance : shifting the imperial gaze - Guhrs, Tamara (Rhodes University, Faculty of Humanities, Department of Drama, 2000)
Nyau Masquerades have been studied by missionaries, anthropologists and religious specialists, but have seldom been documented by theatre and performance specialists. This dissertation argues for the acceptance of Ny au performance as a contemporary world theatre form rooted in tradition. Charting the uneasy relationship between the Nyau and those who have sought to record their performances, the author delineates a vivid dramaturgy of this art form. In doing so, the boundaries of what define theatre as it has traditionally been understood in dominant discourses are made more fluid. Nyau performances have been affected by Colonial processes in varied ways. They were banned by the former government of Northern Rhodesia and severely censored by Catholic Mission teachings in the former Nyasaland. Other forms of vilification have been more subtle. Information about performance in Africa has often been collected and arranged in ways which limit the understanding of these genres. Images of Africa which cluster around the notion of the 'Primitive Other' have enabled a representation of Ny au masking as a superstitious and outdated practice with no relevance for contemporary Africa. This work calls for a new examination of the Nyau, through the lens of local discourse as well as contemporary global understandings of performance. Chapter One examines the issue of primitivism and the ways in which Africa has historically been posited as the exotic Other to Europe. Chapter Two examines the Nyau ih terms of specific dramaturgical elements, adjusting previous misconceptions surrounding the theatr~ forms of Chewa and Nyanja people. Chapter Three is devoted to a discussion of space in ritual theatre and Nyau performance, while Chapter Four explores masking and questions of transformation and liminality. In conclusion, it is seen that the use of the mask is a metaphor for the suspension of rigid boundaries separating subject/object, self/other, ritual/theatre, a suspension which needs to take place before an enriched understanding of performance in Africa can be reached.
Keywords: Masquerades -- Malawi; Masquerades -- Zambia; Malawi -- Religion; Zambia -- Religion; Masks, Chewa; Chewa (African people) -- Rites and ceremonies; Nyanja (African people) -- Rites and ceremonies; Secret societies -- Africa